PENGARUH MOTIVASI TERHADAP PENINGKATAN PRESTASI KERJA PEGAWAI PADA DINAS PENDAPATAN DAERAH KOTA MANADO - Mohamad Arif Umacina; Sonny G. Kaparang; Danny D. S. Mukuan (Universitas Sam Ratulangi, 2015)
Abstract.The purpose of this study was to determine how much influence the motivation onemployee performance. This study uses a quantitative approach by means ofcorrelation and regression analysis. Data collected by using simple randomsampling technique with 49 respondents employees Dinas Pendapatan Daerah in Manado City. The resultsshowed that motivation to have a relationship with job performance but at a lowcategory, but motivation significant effect on employee job performance. Toincrease the motivation of employees, it is necessary to encourage the trainingthat they improve performance.Keywords:Motivation, Job Performance, Employee